Microservice Moving Target Defense Strategy Based on Adaptive Genetic Algorithm - Liu, Xuanyu; Zhang, Shuai; Huo, Shumin; Shang, Ke (Ji suan ji ke xue, 2023)
Microservice architecture can effectively improve the agility of software due to its flexible, scalable and other characte-ristics, and has become the most mainstream method of application delivery in the cloud.However, the microservice splitting makes the attack surface of applications grow explosively, which brings great challenges to the design of mobile target defense strategy with the core of "strategic defense".To solve this problem, a microservice moving target defense strategy based on adaptive genetic algorithm（AGA）,namely dynamic rotation strategy（DRS）,is proposed.Firstly, based on the characteristics of microservice, the attack path of attackers is analyzed.Then, a microservice attack graph model is proposed to formalize various attack scena-rios, and the security gains and return of defense（RoD） of moving target defense strategies are quantitatively analyzed.Finally, AGA is used to solve the optimal security configuration of mobile target defense, that is, the optimal dynamic rotation cycle of mic